125ISOLATION, IDENTIFICATION AND IMMUNOLOGICAL STUDY OF YEAST FROM CATTLE AND BUFFALOES IN BASRAH PROVINCE, IRAQ - Abbas, Basil; H., Khudor; S., Touhali (Iraqi Journal of Science, 2024)
Two hundred samples taken from cattle and buffaloes (50 samples from each urine, blood, tracheal and vaginal swabs) were collected. The study showed that C.albicans was the most common isolates from the total samples. In cattle, it was isolated in a percentage of 50% out of 52 samples, followed by C.krusei 19%, C.parapsilosis 11.5%, C.tropicalis 10%, and C.rugosa 1.9%, on the other hand other isolated yeasts were Cryptococcus neoformans 3.8%,Geotricum candidum 1.9%, and Rhodotorula mucilaginosa 1.9%. In buffaloes C.albicans was also found as a predominant isolates. The total isolates of C.albicans was 43.9% out of 41 samples, followed by, C.tropicalis 22%, C.krusei 19.5%, C.parapsilosis 4.9% and C.rugosa 2.4%. Other yeasts were also identified such as Geotrichum candidum 4.9% and Trichosporom cutaneum 2.4%. C.rugosa was firstly isolated from urine samples taken from cattle and buffaloes and considered as newly recorded species from Iraq. Statistical analysis showed significant difference (P<0.01) between C.albicans isolation comparable with other yeasts in cattle and buffaloes. Using Indirect Immunofluorescent antibody technique, the causative agent can be detected after 12 and 20 days after experimental infection of mice with C.albicans. The result of using disc diffusion method for seven antifungal drugs showed significant differences P<0.01 and P<0.05 on susceptibility of the tested isolates toward antifungal drugs.